Implementasi Model Pembelajaran Problem-Based Learning dengan Bantuan Percobaan Rangkaian Listrik terhadap Peningkatan Hasil Belajar Siswa Kelas V SD - Rossa Puspa Maharani Putri; Umi Mukholifah; Yuni Katminingsih; Nurul Mubarokah (Jurnal Simki Postgraduate, 2024)
This study aims to improve students' learning outcomes in the subject of Social and Natural Sciences on the topic of electrical energy and its applications through the implementation of a problem-based learning model supported by circuit experiments. The research was conducted in the fifth grade of SD Negeri Sukorame 2, Kota Kediri, involving 26 students, consisting of 16 boys and 10 girls. The research method used is classroom action research carried out in two cycles. Each cycle consisted of planning, implementation, observation, and reflection stages. Data were collected through observations and evaluation tests comprising five essay questions administered at the end of each cycle. The results of the study showed an improvement in students' learning outcomes from the first cycle to the second cycle. In the first cycle, the average learning score was 70, with a classical completeness rate of 42.31%. Following the implementation of the problem-based learning model with experimental support, the average learning score in the second cycle increased to 88.5%, with a classical completeness rate of 88.5%, exceeding the predetermined standard. This study demonstrates that problem-based learning accompanied by experiments is effective in enhancing students' understanding of the material, critical thinking skills, and independent learning.